Resistive switching in an organic supramolecular semiconducting ferroelectric - Casellas, Nicolás M.; Urbanavičiūtė, Indrė; Cornelissen, Tim D.; Berrocal, José Augusto; Torres, Tomás; Kemerink, Martijn; García-Iglesias, Miguel (Chemical communications, 2019)
The combination of switchable dipolar side groups and the semiconducting core of the newly synthetized C3-symmetric benzotrithiophene molecule (BTTTA) leads to an ordered columnar material showing continuous tunability from injection- to bulk-limited conductivity modulation.